Erikson Online: Identity and Pseudospeciation in the Internet Age. Issue 4 (2nd October 2018) - Kay, Avi
ABSTRACT: An Eriksonian perspective posits the importance of the societal context in which the individual develops. Part and parcel of that approach is a consideration of how contemporary technology might affect development. This article examines the impact of the defining technology of contemporary society—the Internet—on individual development of Millennials. Specifically, it delineates how the characteristics and affordances of the Internet may impact those elements of identity formation that may contribute to a sense of pseudospeciation. The focus is on the particular challenges of the Internet age on both identity formation and pseudospeciation at a time in which Millennials begin to undertake positions of influence in both their personal and professional lives. The challenges and possibilities inherent in the above are outlined and discussed.